The Response of Mesenchymal Stromal Cells to Cryopreservation within Scaffolds Derived from the Skeletons of Marine Sponges Ianthella basta (Pilot Study) - Mutsenko, Vitaliy V.; Rogulska, Olena Yu.; Tarusin, Dmitriy N. (Problems of Cryobiology and Cryomedicine, 2015)
N/A